Does Urbanization Intensify Carbon Emissions in Nigeria? - Muhammad, Shehu (The European Journal of Applied Economics, 2020)
This study investigates the relationship between urbanization and carbon emissions in Nigeria using Autoregressive Distributed Lag (ARDL) method to analyze the annual time series data spanning from 1974 to 2015. Findings suggests strong positive correlation between urbanization, GDP, energy use and carbon emission, while weak negative correlation exists between trade and carbon emission. We establish from the ARDL result a negatively significant long-run and short-run relationship between urbanization and carbon emission in the Nigerian economy. In the short-run, GDP, energy use and trade have  positive impact on carbon emission while in the long-run, GDP and trade have negative impact on carbon emission with energy use positively impacting carbon emission.  The study therefore concludes that urbanization does not contribute to increase in carbon emission in Nigeria, but energy use does. From our findings, we recommend the use of energy saving and environmentally friendly technology to reduce the amount of carbon emission.